CRIMINAL OFFENSES ARE IN CERTAIN AREAS OF THE AIRPORT WITHOUT PERMISSION FROM THE AIRPORT AUTHORITY - Timbonga, Yotham Th. (Awang Long Law Review, 2023)
Only sometimes flights can be carried out well according to the rules because bad things still happen during their implementation. Aware that undesirable things are still happening at airports, anyone is prohibited from being at the airport without permission from the authorized official; this is in line with the contents of Article 210 of Law Number 1 of 2009 concerning Aviation. This research determines the elements of material offenses for criminal acts of being in certain areas at the airport without permission from the airport authority (study Decision Number 725/Pid.B/2020/PN.Sda). This research uses normative legal analysis with a case and statutory approach. The research materials consist of primary legal materials, namely statutory regulations and judge's decisions. The conclusion in this research is that the material offense element of a criminal act is in a particular area at the airport without permission from the airport authority in Decision Number 725/Pid.B/2020/PN Sda, which is correct because it fulfills the elements in Article 421 paragraph 91) Law Number 1 concerning Aviation, the material aspects of which consist of Any person who is in a particular area at the airport, without obtaining permission from the airport authority as intended in Article 210.